Hepatic Macrosteatosis Is Partially Converted to Microsteatosis by Melatonin Supplementation in ob/ob Mice Non-Alcoholic Fatty Liver Disease - Stacchiotti, Alessandra; Favero, Gaia; Lavazza, Antonio; Golic, Igor; Aleksic, Marija; Korac, Aleksandra; Rodella, Luigi Fabrizio; Rezzani, Rita (PloS one, 2016)
Obesity is a common risk factor for non-alcoholic fatty liver disease (NAFLD). Currently, there are no specific treatments against NAFLD. Thus, examining any molecule with potential benefits against this condition emerged melatonin as a molecule that influences metabolic dysfunctions. The aim of this study was to determine whether melatonin would function against NAFDL, studying morphological, ultrastuctural and metabolic markers that characterize the liver of ob/ob mice. Lean and ob/ob mice were supplemented with melatonin in the drinking water for 8 weeks. Histology and stereology were performed to assess hepatic steatosis and glycogen deposition. Ultrastructural features of mitochondria, endoplasmic reticulum (ER) and their juxtapositions were evaluated in livers of all experimental groups. Furthermore, hepatic distribution and expression of markers of ER and mitochondria (calnexin, ATP sintase β, GRP78 and CHOP) and metabolic dysfunction (RPB4, β-catenin) and cellular longevity (SIRT1) were analyzed. Melatonin significantly reduced glycemia, identified also by a decrease of hepatic RBP4 expression, reversed macrosteatosis in microsteatosis at the hepatic pericentral zone, enlarged ER-mitochondrial distance and ameliorated the morphology and organization of these organelles in ob/ob mouse liver. Furthermore, in ob/ob mice, calnexin and ATP synthase β were partially restored, GRP78 and CHOP decreased in periportal and midzonal hepatocytes and β-catenin expression was, in part, restored in peripheral membranes of hepatocytes. Melatonin supplementation to ob/ob mice improves hepatic morphological, ultrastructural and metabolic damage that occurs as a result of NAFLD. Melatonin may be a potential adjuvant treatment to limit NAFLD and its progression into irreversible complications.